Cyber Sovereignty Gotong Royong, Indonesia’a Way of Dealing with the Challenges of Global Cyber Sovereignty - Nur Ro'is (Pancasila and Law Review, 2022)
State sovereignty is born together with the independence of a country, as well as sovereignty in cyberspace. The state has sovereignty in cyberspace as in its territorial space so that it has jurisdictional authority, but in reality, there are unclear territorial boundaries in cyberspace. Indonesia today still has a dependence on foreign cyberinfrastructure, which causes a high level of cyber vulnerability and low cyber sovereignty resilience. Indonesia has local wisdom known as "Gotong Royong," this conception of local wisdom can be applied to face the global challenges of cyber sovereignty. This study also compares the resilience of Indonesia's cyber sovereignty with the People's Republic of China using a normative legal research methodology with a comparative law approach. Indonesia's limitations in maintaining its cyber sovereignty can be anticipated by using the concept of Gotong Royong cyber sovereignty, which is the implementation of the Universal People's Defense System as regulated in Law Number 3 of 2002 concerning National Defense. The implementation of Cyber Gotong Royong sovereignty involves all citizens, regions, and other national resources.